Persistent intestinal myiasis caused by Oestrus ovis in a Nigerian university student: a case report - Winifred N. Adiri; Bruno Basil; Chinwe P. Onyia; Joy O. Ugwuanyi; Chinyere Azifuaku; Sam C. Iheukwumere; Olivia Obienu; Uchenna N. Ijoma; Sylvester C. Nwokediuko (The Egyptian Journal of Internal Medicine)
Abstract Background Gastrointestinal myiasis is a rare form of infestation by fly larvae which typically occurs due to ingestion of contaminated food or water, especially in regions with poor hygiene. This report presents a rare and persistent case of intestinal myiasis caused by Oestrus ovis in a Nigerian university student, highlighting the challenges posed by persistent symptoms despite prolonged standard anti-helminthic treatments. Case presentation A 24-year-old male Nigerian university student presented with the passage of live maggots in his stool for 1 year likely due to exposure to contaminated food from unsanitary campus vendors. He had received multiple anti-helminthic treatments without improvement. Clinical evaluations, including imaging and laboratory tests, were mostly normal, with live maggots confirmed as Oestrus ovis larvae in stool samples. Initial treatment with standard anti-helminthics failed, leading to prolonged treatment with ivermectin, nitazoxanide, and colonic washes, combined with levofloxacin for Helicobacter pylori eradication, resulting in the resolution of symptoms with no recurrence after 6 months. Conclusion This case emphasizes the need for clinicians to consider rare parasitic infections such as Oestrus ovis myiasis, especially in endemic regions with poor hygiene, and highlights the importance of extended or alternative treatment protocols for resistant cases. It also emphasizes the need for increased awareness of food safety and hygiene in high-risk environments and further research into resistance mechanisms in myiasis treatment.